Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1128/aac.46.2.514-516.2002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Terbinafine in Mouse and Rat Models ofPneumocystis cariniiPneumonia

Abstract: Terbinafine, an allylamine used to treat onychomycosis, has been reported to be active against rat Pneumocystis carinii in vitro and in vivo. By contrast, our in vitro data showed that the 50% inhibitory concentration of terbinafine against rat P. carinii is 3.7 g/ml, a level that cannot be clinically achieved in serum. In the present study, terbinafine administered orally at doses of 20 to 400 mg/kg/day and 50 to 250 mg/kg/day was ineffective therapy for mouse and rat models of pneumocystosis, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It may because 100 mg/ kg/day terbinafine was toxic, even if an 80 mg/kg/day dose was not. Concerning this, Walzer et al [17] tested terbinafine in mouse and rat models of Pneumocystis carinii pneumonia in doses of 20-50-150 mg/kg/day in mice and 50-250 mg/kg/day in rats. The authors found that these therapies were ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may because 100 mg/ kg/day terbinafine was toxic, even if an 80 mg/kg/day dose was not. Concerning this, Walzer et al [17] tested terbinafine in mouse and rat models of Pneumocystis carinii pneumonia in doses of 20-50-150 mg/kg/day in mice and 50-250 mg/kg/day in rats. The authors found that these therapies were ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning 1 day after infection, one group remained untreated (the control group), three other groups were treated with fluconazole (Pfizer) at 100mg/kg/day in 0.2 ml i.p., with amphotericin B 1 mg/kg/day ip, and with terbinafine 100mg/kg/day by oral gavages. [1,2,13,17] The remaining two groups were treated with terbinafine with amphotericin B and terbinafine with fluconazole at the same doses. Treatment was continued up to day 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The investigators of two studies found that terbinafine given at oral doses of 15 to 80 mg/kg/day had an efficacy equal to or greater than that of known anti-P. carinii drugs in rats with PCP. [5,6] In another study Walzer et al [1] showed that terbinafine administered orally at doses of 20 to 400 mg/kg/day and 50 to 250 mg/kg/day was ineffective therapy for mouse and rat models of pneumocystosis, respectively.…”
mentioning
confidence: 99%
“…Drugs used in PCP in clinical use are hampered by toxicity, limited effectiveness, and emerging resistance. [1,2] The lack of interest among pharmaceutical companies in developing new agents for Pneumocystis has stimulated efforts to test existing drugs marketed for other purposes for activity against the organism. Terbinafine is an allylamine antifungal agent which appears to act by preventing fungal ergosterol biosynthesis via specific and selective inhibition of fungal squalene epoxidase.…”
mentioning
confidence: 99%